Teratogenic Test of Jamblang Fruit Extract (Syzygium cumini) on the Fetus Mice (Mus musculus) - Dewi, Cut Nur Kemala; Sari, Ayu Nirmala; Hayatillah, Raudhah (Universitas Sultan Ageng Tirtayasa, 2025)
Jamblang fruit (Syzygium cumini) is used to treat diabetes mellitus, pain, inflammation, ulcers, and diarrhea, and in recent research, it has been proven to be used as a chemopreventive, radioprotective, and antineoplastic. Jamblang fruit contains several ingredients, namely: alkaloids, saponins, tannins, triterpenoids, flavonoids, polyphenols, and buchard. However, it is necessary to ensure whether jamun is safe for consumption by pregnant women, and a teratogenic test is needed. This research aims to determine the effect of jamblang fruit extract on maternal weight, number of fetuses, fetal length, fetal weight, hemorrhage, and morphological abnormalities in the fetus. This research is included in quantitative research using experimental methods with a Completely Randomized Design (CRD), which consists of 4 treatments and 5 replications. The experimental animals used were 20 female mice (Mus musculus) of the Balb/C strain, healthy mice aged 2 months, weighing 27-30 grams, and the mice were mature and ready to mate. Mice were divided into 4 treatment groups, namely the control group, the 100 mg/kgBB dose group, the 200 mg/kgBB dose group, and the 300 mg/kgBB dose group. Treatment doses of jamun fruit extract 70% ethanol are given on days 6 to 17 of pregnancy. Data analysis using SPSS showed that ethanol 70 % extract of jamblang fruit had no effect on maternal weight and fetal weight in mice (>0.05), but did affect fetal length, number of fetuses, hemorrhage, and morphological abnormalities in the form of open eyelids (p<0.05). Based on the research results, it can be concluded that administration of jamblang fruit ethanol extract can reduce fetal length and the number of fetuses. The 200 mg/kgBB and 300 mg/kgBB dose groups are doses that can cause teratogenic effects such as hemorrhage and open eyelids.